Outbreak of Contagious Echtyma in Sheep in Rio Grande do Sul, Brazil. - Panziera, Welden; Lorenzett, Marina Paula; Hammerschmitt, Márcia Elisa; Slaviero, Mônica; Cardoso, Henriqque Mondardo; Pavarini, Saulo Petinatti; Driemeier, David (Acta Scientiae Veterinariae, 2016)
Background: Contagious ecthyma is a viral disease caused by a Parapoxvirus, which affects primarily sheep and goats. The disease has a worldwide distribution and is characterized by cutaneous pustules and crusts mainly in the muzzle and lips. Although the disease has a worldwide distribution, there are few reports in the literature of contagious ecthyma outbreaks in Brazil. Moreover, this is an important disease, as well as causing huge economic losses due to high morbidity rates, is also a zoonosis occupational character. This report describes the epidemiological, clinical, and anatomopathological aspects of an outbreak of contagious echtyma in sheep in the State of Rio Grande do Sul, Brazil. Case: Cases were observed on January and February of 2016. Seventeen out of 45 Texel sheep were affected including fve 4-6-month-old lambs, three 7-12-month-old male sheep and nine 2-year-old ewes. Before the outbreak, a Texel ram was introduced in the herd as replacement. Clinically, affected sheep had pustules, ulcers, and crusts in the lips, labial commissures, muzzle, and nasal bridge. They also presented dyspnea, submandibular and facial subcutaneous edema. One of the affected sheep was euthanized due to the poor prognosis. At necropsy, the lesions observed clinically were confrmed. Histopathology of the skin in the lips and muzzles showed marked acanthosis of the epidermis, orthokeratotic and parakeratotic hyperkeratosis of the stratum corneum, intracorneal vesicles and pustules, as well as hydropic degeneration and apoptosis of keratinocytes. This lesions led to epidermal serocellular crusting. Histologically and ultrastructurally respectively, inclusion bodies or viral particles were not observed. Approximately 45 days after the diagnosis there were no new cases of echtyma in the herd. Discussion: The diagnosis of contagious ecthyma in these sheep was based on epidemiological, clinical, and pathological fndings. In sheep and goats the disease affects mainly lambs, kids, and lactating females, although sheep from both sexes, and all breeds and ages are susceptible. In this outbreak, sheep of different categories were affected with morbidity about 37%. Carrier sheep and contaminated fomites are the main forms of transmission. In this outbreak, it is presumed that the introduction in the herd of a male carrying the virus was the source of infection to the other sheep. Clinically, it was notice a variation in the clinical signs. Initial lesions were almost imperceptible, and latest lesions were more severe, with a predominance of proliferative crusted changes in the lips and muzzle. The facial and submandibular edema in some sheep was an unusual manifestation of the disease. Gross and microscopic fndings observed in these sheep contributed to the defnitive diagnosis of the disease. Histologically, despite inclusions were not observed, hyperkeratosis, acanthosis, pustules, and degenerative and necrotic changes in the epithelium are typical lesions of contagious ecthyma. It is suggested that the viral particles and the inclusion bodies were not detected by electron microscopy and histology because the necropsied sheep presented a chronic clinical course of the disease. The association of epidemiological, clinical, and pathological fndings allowed the defnitive diagnosis of contagious ecthyma, although inclusions and viral particles were not observed. The introduction of a virus carrier was the likely source of the disease in a non-immune herd. Keywords: diseases of sheep, viral diseases, Parapoxvirus, pustular dermatitis, orf